Corrosion behavior of titanium alloys (Ti CP2, Ti-6Al-2Sn-4Zr-2Mo, Ti-6Al-4V y Ti Beta-C) with anodized and exposed in NaCl and H2SO4 solutions - Gaona Tiburcio, Citlalli; Jáquez Muñoz, Jesús Manuel; Nieves Mendoza, Demetrio; Maldonado Bandala, Erick; Lara Banda, María del Refugio; Lira Martínez, Manuel Alejandro; Reyes Blas, Hortensia; Baltazar Zamora, Miguel Ángel; López León, Luis Daimir; Almeraya Calderón, Facundo (Molecular Diversity Preservation International, 2024)
Nowadays, different industries, such as the aerospace and biomedical industries, prefer using Ti alloys due to their excellent anti-corrosion properties and ability to generate a TiO2 oxide layer; this induces the use of anodization to increase the useful life of components. The aim of this work is to characterize the electrochemical effect of anodizing treatment on titanium alloys (Ti CP2, Ti-6Al-2Sn-4Zr-2Mo, Ti-6Al-4V, and Ti Beta-C) in NaOH and KOH at 1M, applying a current density of 0.0025 A/cm2. The electrochemical techniques employed were lectrochemical noise (EN) and electrochemical impedance spectroscopy (EIS), supported by ASTM G199 and ASTM G106 in electrolytes of NaCl and H2SO4 at 3.5 wt. % as a simulation of marine and industrial atmospheres. Also, the anodized transversal section and surface morphology were characterized by a scanning electron microscope (SEM). The results of both electrochemical techniques indicated that Ti-6Al-2Sn-4Zr-2Mo anodized in NaOH presented the best properties against corrosion, and the thickness of the oxide was the biggest.